Internalization of Islamic Religious Education Values among Gen Z Students through ROHIS: A Study at SMA Negeri 1 Gemolong - Khofifah Az Zahra; Shokhibul Mighfar; Desti Widiani (Konsultan Jurnal Ilmiah Indonesia, 2026)
The rapid development of technology has led to deviant behaviors among teenagers, such as dating, smoking or vaping, and bullying. Limited PAI learning in class makes ROHIS activities an important alternative for internalizing Islamic values among Gen Z students at SMA Negeri 1 Gemolong. This research aims to explain the internalization process of PAI values and identify supporting and inhibiting factors. The subjects are ROHIS members. Using a descriptive qualitative approach, data was collected through interviews, observation, and documentation. Results show the internalization process through ROHIS aligns with the ROHIS Work Program Plan, including daily (WhatsApp channel), weekly (routine studies, mosque cleaning, and da'wah posters and videos), and annual programs (Ta'aruf, zakat management, Pesantren Kilat, Bukber and Sarasehan, Takjil distribution, training, grand study and talkshow, and social service). This aligns with ROHIS's vision and mission. Internalization occurs in three stages: 1) value transformation through WhatsApp, routine studies, da'wah posters and videos, Pesantren Kilat, training, and grand study; 2) value transaction through mosque cleaning, da'wah posters and videos, Ta'aruf, zakat management, Bukber and Sarasehan, Takjil distribution, and social service; 3) transinternalization of values, embedding morals towards Allah, humans, and the environment. Methods used include exemplary, habituation, motivation, and rule enforcement. Supporting factors include clear ROHIS vision and mission, support from coaches and PAI teachers, and internal motivation of ROHIS members. Inhibiting factors include suboptimal social media use and limited time and activity schedules.